2019
DOI: 10.3390/ijerph16030400
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Use Practices in Root, Tuber, and Banana Crops by Smallholder Farmers in Rwanda and Burundi

Abstract: Misuse and poor handling of chemical pesticides in agriculture is hazardous to the health of farmers, consumers, and to the environment. We studied the pest and disease management practices and the type of pesticides used in four root, tuber, and banana (RTB) crops in Rwanda and Burundi through in-depth interviews with a total of 811 smallholder farmers. No chemical pesticides were used in banana in either Rwanda and Burundi, whereas the use of insecticides and fungicides in potato was quite frequent. Nearly a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This underlines the importance of meeting safety requirements, including the provision of protective clothing. An observed persistence or worsening of dangerous working conditions is often fostered by a lack of information in the affected population and a lack of general education, as well as a lack of specific training for farmworkers and sometimes also by missing or neglected execution of legal measures [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the importance of meeting safety requirements, including the provision of protective clothing. An observed persistence or worsening of dangerous working conditions is often fostered by a lack of information in the affected population and a lack of general education, as well as a lack of specific training for farmworkers and sometimes also by missing or neglected execution of legal measures [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The use of pesticides on sweetpotato is very low in SSA, except in Nigeria and Uganda, where use is increasing (Reynolds et al, 2015). Okonya et al (2019) reported that 14% of farmers surveyed in Rwanda and Burundi used insecticides on sweetpotato, while none used herbicides or fungicides.…”
Section: Pest and Disease Managementmentioning
confidence: 99%
“…Furthermore, it matters how farmers access pesticides. One particularity of smallholder's pesticide use is their dependence on unauthorized dealers, who often sell products of dubious quality and origin (Ndayambaje et al, 2019;Negatu et al, 2016;Okonya et al, 2019) and with limited knowledge about the products (Yami & van Asten, 2018). Many SSA countries struggle with the problem of illegally sold and/or counterfeit agrochemicals, which may be adulterated or contain banned compounds (Ashour et al, 2019;Okolle et al, 2016).…”
Section: The Specific Vulnerabilities Of Smallholdersmentioning
confidence: 99%